Evaluation of common errors of panoramic radiographs in Tabriz Faculty of Dentistry - Farzad Esmaeili; Masume Johari; Farzaneh Kaviani (Tabriz University of Medical Sciences, 2008)
Background and aim. Knowledge of the common radiographic errors and their prevention could prevent imposing redundant radiation, time and money to patient and the dentist. The aim of this study was to assess the common radiographic errors on panoramic radiographs in a radiology department.
Materials and methods. 250 panoramic radiographs (100 male and 150 female; mean age, 24.3) taken at the Department of Oral and Maxillofacial Radiology were evaluated. Radiographs were categorized into five groups according to the type of errors (patient positioning errors, darkroom errors, failure to remove metallic accessories, equipment setup errors, and patient movement during exposure).
Results. There were19 error-free radiographs. The number of radiographs with errors was 231, of which 26 were unacceptable and had to be retaken. Errors of patient positioning were observed in 78% of cases, film development in 69.2%, equipment setup in 3.2%, failure to remove metallic accessories in 3.2% and patient movement during exposure in 2.4% of cases.
Conclusion. The errors seen on panoramic radiographs were relatively high with errors in patient positioning being the most frequent error.